What's Going On? (In Modern Texas Folklore) - Abernethy, Francis Edward; Open Access Publishing in European Networks; Project Muse. (College Station : Texas A & M University Press [distributor], 1998)
Annotation This collection of essays from the 1970s describes the customs, traditions, songs, and stories by which future anthropologists will analyze that decade. The rodeos and chain letters and bumper stickers, Neiman Marcus and fat stock shows, gospel conventions and underground newspapers, CB radios and university ghosts, backwoods beer busts and the folklore of marijuana, Jack Ruby and the Kennedy assassination. This publication also looks at zydeco, Western Swing, gospel music, Texas country music, and the rise of redneck rock, by such writers as Joseph Lomax, Guy Logsdon, Bill Malone, and Jan Reid.
Description based on print version record.
Keywords: Social Science -- Folklore & Mythology; Folklore -- United States; Electronic book; Electronic books